2021
DOI: 10.1371/journal.pone.0258513
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of hospitalisation and intensive care admission associated with reported cases of SARS-CoV-2 variants B.1.1.7 and B.1.351 in Norway, December 2020 –May 2021

Abstract: Introduction Since their emergence, SARS-CoV-2 variants of concern (VOC) B.1.1.7 and B.1.351 have spread worldwide. We estimated the risk of hospitalisation and admission to an intensive care unit (ICU) for infections with B.1.1.7 and B.1.351 in Norway, compared to infections with non-VOC. Materials and methods Using linked individual-level data from national registries, we conducted a cohort study on laboratory-confirmed cases of SARS-CoV-2 in Norway diagnosed between 28 December 2020 and 2 May 2021. Varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 17 publications
4
32
0
1
Order By: Relevance
“…In this study, we have analysed individual-level data on laboratory-confirmed cases of COVID-19 in Norway and hospitalisations among cases within the study period, as well as demographic characteristics, vaccination status and underlying comorbidities. Earlier analyses of other VOC in Norway showed an increased risk of hospitalisation for Alpha and Beta compared to non-VOC (Veneti et al, 2021), in line with others (Bager et al, 2021a;Funk et al, 2021;Grint et al, 2021;Fisman and Tuite, 2021). Here our findings indicate no difference in the risk of hospitalisation for SARS-CoV-2 cases infected with the Delta variant compared to the Alpha variant in Norway, in contrast to published estimates from other countries.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, we have analysed individual-level data on laboratory-confirmed cases of COVID-19 in Norway and hospitalisations among cases within the study period, as well as demographic characteristics, vaccination status and underlying comorbidities. Earlier analyses of other VOC in Norway showed an increased risk of hospitalisation for Alpha and Beta compared to non-VOC (Veneti et al, 2021), in line with others (Bager et al, 2021a;Funk et al, 2021;Grint et al, 2021;Fisman and Tuite, 2021). Here our findings indicate no difference in the risk of hospitalisation for SARS-CoV-2 cases infected with the Delta variant compared to the Alpha variant in Norway, in contrast to published estimates from other countries.…”
Section: Discussionsupporting
confidence: 90%
“…Alpha has been shown to be more easily transmitted than non-VOC variants (Davies et al, 2021), and was the dominant circulating SARS-CoV-2 variant in Norway during the third wave of infections in the winter and spring of 2021. It was also associated with a 1.9-fold increased risk of hospitalisation compared to non-VOC variants (Veneti et al, 2021). Similar associations were observed in other European countries (Bager et al, 2021a;Funk et al, 2021;Grint et al, 2021).…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, the differences in the risk of mortality mainly came from Funk et al (31) and Martínez-García et al (43) wherein they concluded that the mortality rate was reduced, and Stirrup et al (49) concluded that the mortality rate was equivalent. For the Beta variant compared to wildtype virus, Funk et al (31), Fisman and Tuite, (35), and Veneti et al (46) found that it increased the risk of hospitalization and ICU admission. In addition, Funk et al (31) and Fisman and Tuite, (35) reported that Beta variant also increased the risk of mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Less prevalent than the alpha and delta variants, the beta variant accounted for approximately 10% of virus samples in France in June 2021 (https://www.santepubliquefrance.fr/). Mutations in the beta variant make it more transmissible, with greater antibody resistance, higher risk of hospitalization, ICU admission, and death compared to earlier SARS-CoV-2 E variants (Veneti et al, 2021; Wang et al, 2021). In addition to the P71L mutation, the beta variant has other mutations, including three on its spike protein, which may help the virus to escape antibodies and to bind more tightly to human cells (Han et al, 2021).…”
Section: Discussionmentioning
confidence: 99%